Clinical Depression and Punishment Sensitivity on the BART - Hevey, David; Thomas, Kevin; Laureano-Schelten, Sofia; Looney, Karen; Booth, Richard (Frontiers in Psychology, 2017)
Depression is associated with altered sensitivity to reward and punishment, which can influence complex decision-making. We examined punishment sensitivity in the performance of participants with Major Depressive Disorder (MDD) with that of a comparison group on the automatic Balloon Analogue Risk Test (BART), which is a direct measure of risk taking. The present study examined the BART performance of 30 individuals with MDD and 30 matched comparison individuals. The comparison group (Mean = 63.25) entered a significantly (p < .001; d = 1.1) higher number of pumps on the BART than the MDD group (Mean = 50.83). Higher levels of depression symptoms were significantly correlated (r = -0.40, p < .05) with entering a lower number of pumps in the MDD group. MDD patients showed an increased sensitivity to punishment on the BART: after a loss, the MDD group decreased (Mean = 13.7) the number of subsequent pumps they entered by a significantly (p < .001, d = 0.81) greater amount than the comparison group (Mean = 4.35). This difference applied to losses only: no difference was found between the groups regarding the magnitude of change in pumps selected after a win. Findings suggest the presence of elevated punishment sensitivity among individuals with MDD, which may contribute to the maintenance of depressive symptoms